Determinants of Accountant Involvement Intentions in Sustainability Accounting Practices - Nurmalia Malahusna; Niko Silitonga (Universitas KH. Abdul Chalim Mojokerto, 2026)
The role of accountants in sustainability accounting practices is a determining factor in the transformation of the accounting profession amidst demands for transparency, social responsibility, and organizational sustainability. This study aims to analyze the determinants of accountants' involvement in sustainability accounting practices using the Theory of Planned Behavior (TPB) framework. This study used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique on 252 respondents who work as accountants. The results show that perceived benefits have a positive and significant effect on attitudes toward sustainability accounting and intentions to engage in sustainability accounting, while perceived costs and complexity do not affect attitudes toward sustainability accounting but have a negative and significant effect on intentions to engage in sustainability accounting. In addition, attitudes toward sustainability accounting are proven to have a positive effect on intentions to engage in sustainability accounting and are able to mediate the relationship between perceived benefits and intentions to engage in sustainability accounting, but do not mediate the relationship between perceived costs and complexity and intentions to engage in sustainability accounting. Overall, these findings confirm that perceived benefits and the formation of positive attitudes are key factors in encouraging accountants' involvement in sustainability accounting practices, while perceived costs and complexity need to be managed strategically to avoid becoming obstacles to implementation.